DISTRIBUTION OF HORSES GLANDERS IN THE WORLD AND COUNTRIES BORDERING WITH KAZAKHSTAN - Alikhanov, K. D.; Abultdinova, A. B.; Syrym, N. S.; Espembetov, B.; Tagayev, O. O. (Ғылым және білім=Наука и образование=Science and education № 3-1 (68), 2022)
Glanders (malleus) is an infectious disease of horses, donkeys, mules and others hoofed animals characterized by the formation of specific nodules prone to necrosis. Glanders is caused by bacteria of the species Burkholderia mallei, can also be transmitted to humans. In recent years, the republic has taken a course to increase the number of horses. That is the reasons for large investments are allocated for the purchase of breeding cattle from countries near and far abroad. At the same time, there is a danger of the introduction of a dangerous zoonotic disease – glanders from high-bacteria areas countries. In this regard, the study of the epizootic situation of outbreaks of equine glanders is of undoubted practical interest. The epizootic situation of horse breeding in the world and the republic was studied by analyzing the veterinary reporting data of the Committee for Veterinary Control and Supervision of the Ministry of Agriculture of the Republic of Kazakhstan, as well as according to the OIE (The World Organization for Animal Health). Сап (malleus) - инфекционная болезнь лошадей, ослов, мулов и других непарнокопытных семейства лошадиных, характеризующаяся образованием специфических сапных узелков, склонных к некрозу. Сап вызывается бактериями вида Burkholderia mallei, может также передаваться человеку. В республике в последние годы взят курс на увеличение поголовья лошадей. С этой целью выделяются большие инвестиции для приобретения племенного скота из стран ближнего и дальнего зарубежья. При этом существует угроза заноса особо опасной зоонозной болезни – сап из неблагополучных стран. В связи с этим изучение эпизоотической ситуации вспышек заболеваемости сапа лошадей представляет несомненный практический интерес.
Keywords: отечественное издание; научный журнал; журнал коксон; периодическое издание; ринц; сап; болезнь лошадей; инфекционная болезнь; glanders; horses; malleinization; epizootic situation